Qualidade de vida relacionada à saúde em homens e mulheres com alopecia androgenética em uso de terapia com luz de baixa intensidade - Quirino, Leonardo de Medeiros (2020)
Introduction: Androgenetic alopecia (AGA) is the most common cause of hair loss in men and women, and it can affect the psychological and social activities of individuals, thus reducing their health-related quality of life (HRQoL). The Low-Level Light Therapy (LLLT) is a recent adjuvant treatment for this condition with promising results for hair regrowth. Objective: We aimed to assess the HRQoL of men and women with AGA before and after LLLT sessions. Material and methods: This is a single-center prospective observational study conducted with 36 men and 35 women with AGA. All participants answered a sociodemographic questionnaire in an interview and individually answered the Brazilian version of Skindex-29 (selfapplication). After 24 LLLT sessions, two 20-minute sessions per week, with 48 to 72 hours of an interval between sessions, participants answered the Skindex-29 again. Results: Women had a large reduction in Skindex-29 total score after LLLT (p<0.01; d=0.82) and lower scores in the emotions (p<0.01; d=0.89), psychosocial functioning (p<0.01; d=0.60) and symptoms domains (p=0.03; d=0.38). Men presented a moderate reduction in Skindex-29 total score after LLLT (p<0.01; d=0.68), largely lower scores in the emotions domain (p<0.01; d=0.82), and a small reduction in the psychosocial functioning domain (p<0.01; d=0.47). Symptoms also decreased, but with p=0.06. Conclusion: The use of LLLT in AGA is associated with an improvement in the HRQoL of men and women. The impact was higher regarding emotions, the major domain affected in the AGA population. Women had larger impacts on all domains of Skindex-29 after the use of LLLT.